Aortic aneurysms and markers of platelet activation, hemostasis, and endothelial disruption in people living with HIV - Grønbæk, Sylvester Klöcker; Høgh, Julie; Knudsen, Andreas Dehlbæk; Pham, Michael Huy Cuong; Sigvardsen, Per Ejlstrup; Fuchs, Andreas; Kühl, Jørgen Tobias; Køber, Lars; Gerstoft, Jan; Benfield, Thomas; Ostrowski, Sisse Rye; Kofoed, Klaus Fuglsang; et al. (Frontiers in Immunology, 2023)
Introduction People living with HIV (PLWH) are at twice the risk of developing cardiovascular diseases and have more than four times higher odds of aortic aneurysm (AA) than the uninfected population. However, biomarkers of AA in PLWH are yet to be discovered. We aimed to investigate whether circulating biomarkers reflecting platelet activation, hemostasis and endothelial disruption, i.e. sCD40L, D-dimer, syndecan-1, and thrombomodulin, were associated with AA in PLWH. Methods Five hundred seventy one PLWH from the Copenhagen Comorbidity in HIV Infection (COCOMO) study ≥40 years of age with an available contrast-enhanced CT scan as well as available biomarker analyses were included. The biomarkers were analyzed on thawed plasma. For each biomarker, we defined high level as a concentration in the upper quartile and low level as a concentration below the upper quartile. For D-dimer, the cut-off was defined as the lower limit of detection. Using unadjusted and adjusted logistic and linear regression models, we analyzed associations between AA and sCD40L, D-dimer, syndecan-1, and thrombomodulin, respectively in PLWH. Results PLWH had median (IQR) age 52 years (47-60), 88% were male, median (IQR) time since HIV diagnosis was 15 years (8-23), and 565 (99%) were currently on antiretroviral treatment. High level of sCD40L was associated with lower odds of AA in both unadjusted (odds ratio, OR, 0.23 (95% CI 0.07-0.77; P=0.017)) and adjusted models (adjusted OR, aOR, 0.23 (95% CI 0.07-0.78; P=0.019)). Detectable level of D-dimer was associated with higher odds of AA in both unadjusted (OR 2.76 (95% CI 1.34-5.67; P=0.006)) and adjusted models (aOR 2.22 (95% CI 1.02-4.85; P=0.045)). Conclusions SCD40L was associated with lower odds of AA whereas D-dimer was independently associated with higher odds of AA in PLWH. This calls for further investigations into specific biomarkers to aid early diagnosis of AA in PLWH.